(untitled) (Canadian Medical Education Journal, 2021)
Implication Statement Selkirk College’s Rural Pre-Medicine (RPM) program launched in 2014 as a unique undergraduate initiative designed to increase the number of students who prepare for future careers in rural healthcare and, in the longterm, to play a role in reducing rural health disparities. Preliminary evaluation indicates most students in the program have rural backgrounds and the majority of graduates with follow-up data go on to further health science programming, including medical school. Challenges with retention have been identified. RPM is committed to ongoing program improvement and to providing a model for similar programs in other jurisdictions.